Implementasi Program Keluarga Harapan (PKH) dalam Upaya Pengentasan Kemiskinan di Kecamatan Banjarsari Kota Surakarta Tahun 2020-2021 - Shafira Twinsa Diaz; Priyanto Susiloadi (Universitas Sultan Ageng Tirtayasa, 2023)
PKH is a conditional cash transfer program by Indonesian government that focus on accelerating poverty alleviation on education, health and social welfare. In 2020-2021 PKH policy change due to the Covid-19 pandemic phenomenon, the program implementation transform from the conventional era to the digitalization era, other problems is KPM not being right on target, lack of awareness of KPM to be independent and consistent on program requirements. The purpose of this study to analyze implementation of PKH 2020 - 2021 in Banjarsari District, Surakarta City used George Edward III implementation theory model specifically on four aspects: bureaucratic structure, disposition, resources, communication and also reviewing the supporting and inhibiting factors of PKH implementation. This research is a qualitative descriptive with data collection techniques through interviews, observation, and documentation. The technique of determining informants is by purposive sampling technique, data validity using a validity of source triangulation, data analysis technique using Milles and Huberman's interactive data analysis.The results of the study show that the implementation of PKH in Banjarsari District through the communication, resources, disposition, and bureaucratic structure aspects has been running by central and regional government regulations with various changes in conditions during the Covid-19 pandemic. Supporting factors are support from stakeholders, facility and budget resources and beraucratic structure. Inhibiting factors are the changing of policies, KPM not being right on target and lack of awareness to be independent and consistent on program requirements, limited space for PKH facilitators due to Covid-19 pandemic and lack of human resources.